\(a,-x^4\left(yx\right)^2\left(-x\right)^2\left(-y\right)^3=x^8y^5\)
\(\dfrac{1}{2}ax^3\left(-xy\right)\left(-y\right)^2=\dfrac{1}{2}ax^4y^2\)
\(-\dfrac{4}{5}y\left(\dfrac{3}{2}x^2y\right)^4=-\dfrac{81}{20}x^8y^5\)
Đúng 0
Bình luận (2)
b, \(\dfrac{1}{2}ax^3\left(-xy\right)\left(-y\right)^2\)
\(=-\dfrac{a}{2}x^4y^3\)
c, \(-\dfrac{4}{5}y\left(\dfrac{3}{2}x^2y\right)^4\)
\(=-\dfrac{4}{5}y.\dfrac{81}{16}x^8y^4=-\dfrac{81}{20}x^8y^5\)
Chúc bạn học tốt!!!
Đúng 0
Bình luận (1)
Toshiro KiyoshiAkai HarumaHồng Phúc NguyễnNguyễn Huy TúT.Thùy Ninh
Đúng 0
Bình luận (0)